The role of prefixes in the formation of aspectuality Issues of grammaticalization - BENACCHIO, ROSANNA; Muro, Alessio; Slavkova, Svetlana (Biblioteca di Studi Slavistici, 2017)
One of the most widely debated topics in Slavic linguistics has always been verbal aspect, which takes different forms because of the various grammaticalization paths which led to its emergence. In the formation of the category of aspect in Slavic languages, a key role was played by the morphological mechanism of prefixation (a.k.a. preverbation), whereby the prefixes (which originally performed the function of markers of adverbial meanings) came to act as markers of boundedness. This volume contains thirteen articles on the mechanism of prefixation, written by leading international scholars in the field of verbal aspect. Ancient and modern Slavic varieties, as well as non-Slavic and even non-Indo-European languages, are represented, making the volume an original and significant contribution to Slavic as well as typological linguistics.